Strategi Penanganan Pembiayaan Murabahah Bermasalah (Studi PT. BPRS Siak Jaya Kabupaten Siak, Riau) - Asrial Saputra; Indah Rahmawati (AMAL: Jurnal Ekonomi Syariah, 2025)
PT. BPRS Siak Jaya as one of the financial intermediary institutions whose activities are to collect public funds in the form of deposits and re-channel them in the form of financing. However, in providing financing to customers, it cannot be separated from various risks, one of which is non-performing financing which results in a decrease in the level of bank liquidity and also affects the decrease in the level of trust of depositors who entrust their money. The purpose of this study is to determine the factors causing the occurrence of problematic murabahah financing, and strategies in dealing with problematic murabahah financing at PT. BPRS Siak Jaya. This research uses a qualitative method approach. Data collection techniques in this research are interviews, observations and documentation. The results of the study found that: First; There are two factors that cause problematic murabahah financing, namely internal and external factors. The internal factors are the weakness of BPRS in financing analysis, financing documents, collateral and human resources. Meanwhile, external factors are weaknesses in the character of the customer, the ability of the customer and the calamity experienced by the customer. Secondly; strategies in dealing with problematic murabahah financing at BPRS Siak Jaya are approach to customers, intensive collection, provision of letters of reprimand (SP 1,2, and 3), restructuring process by rescheduling and finally execution/liquidation of collateral.